Nutritional Composition and Antioxidant Properties of Cucumis dipsaceus Ehrenb. ex Spach Leaf - Rahul Chandran; V. Nivedhini; Thangaraj Parimelazhagan (The Scientific World Journal)
The leaf of C. dipsaceus was evaluated for its nutritional and antioxidant properties. From the present investigation, significant amount of almost all essential amino acids and important minerals were quantified. Low levels of trypsin inhibitory units, phenolics, and tannins content were found as antinutritional content. Further, hot water extract of C. dipsaceus showed good activity especially in ABTS+, metal chelating, nitric oxide, and DPPH assays. Hence, the results conclude that C. dipsaceus could be a valuable nutraceutical supplement to the human diet.